Poland - Skorupska, Adriana (The Role of Regions in EU-China Relations, 2021)
The first objective of the chapter is to characterize the activities between Polish regions and Chinese provinces and cities – their intensity, scope, advantages and obstacles. When it comes to a broader perspective – the bilateral state government relations – the chapter answers the question whether there is any correlation between relations at the state level and at the regional level. Moreover, taking into consideration that one of the main objectives for the whole project is to analyse the correlation between the EU-China relations and paradiplomacy, the question is: do the voivodeships see any role for the EU in their activities with Chinese partners? Do they need any support from the Union to have more intense and effective cooperation?